병원다각화 결정요인 분석 - 조동영(Dong-Young Cho); 서원식(Won-Sik Suh) (대한경영학회지, 2014)
이 연구는 우리나라 병원의 전반적인 다각화수준 및 병원 조직의 내 ․ 외적 환경요인에 따라 다각화수준의 차이를 분석하고, 나아가 다각화에 영향을 미치는 요인을 포괄적으로 분석하여 재무건전성 확보를 위한 유용한 정보를 제공하기 위해 시도되었다. 2008년부터 2012년까지 대한병원협회에서 실시한 병원표준화심사 대상 병원 중 722개 종합병원의 자료를 분석한 주요 결과는 다음과 같다. 첫째, 다각화의 환경요인별로 다각화수준의 차이가 있는지를 분석한 결과, 병상규모가 큰 병원, 대학병원, 대도시에 위치한 병원, 경쟁 정도가 심한 병원, 경영위험이 높은 병원, 부채비율이 높은 병원일수록 다각화수준이 유의하게 높았다. 둘째, 변수 간 관계를 고려한 회귀식 모형에서 병원경영다각화에 통계적으로 유의한 영향변수는 설립형태(국공립병원/민간병원), 부채비율, 대학병원유무(대학병원/비대학병원)였다. 즉, 민간병원이 국공립병원에 비해 다각화 수준이 높았고, 부채비율이 높을수록 다각화수준도 높았다. 또한 대학병원이 비대학병원에비해 다각화 수준이 높았다. The purpose of this study was to examine financial, market, organizational determinants ofhospital diversification in order to guide hospital managers in undertaking such diversificationefforts in Korea. The study utilized 722 hospitals that passed the standardization audit undertakenby the Korean Hospital Association from 2008 to 2012. Major findings were as follows. First, significant differences were found in the average level of diversification in thedeterminants of hospital diversification adopted in this study. Hospitals with larger size, located incompetitive market, with higher business risk, with higher debt-ratio, and university hospitals areshown higher diversification index compared to control groups. Second, after controlling for selection bias, private hospitals, university hospitals, and debt ratioare predictors of hospital diversification, and they were statistically significant. In other words, Itis more likely to have strong relationship between diversification and determinants if they areprivate hospital over public, higher debt ratio, and university hospital. KCI Citation Count: 5